Measuring Vietnamese-speaking English as a foreign language students’ socio-emotional skills - Hung, Do Minh; Anh, Le Thanh Nguyet; Ngan, Vo Phan Thu; Tac, Pham Van; Tinh, Bui Thanh (International Journal of Evaluation and Research in Education (IJERE), 2025)
Socio-emotional skills are crucial in learning processes and academic performances, but research in this field among college students, especially among Vietnamese-speaking students majoring in English as a foreign language (EFL) is still rare. Thus, the study attempts to fill this gap. As the first necessary part of a larger research project, the present study measured the target population’s socio-emotional skills via a 30-item questionnaire scale made up of two core components (the self and the others) embracing five subcomponents (self-awareness, self-regulation, self-utilization, empathy, and social skills). The sample group of 615 EFL majors from a university in Vietnam was surveyed. Statistic survey results show that the group appeared to reach a high level of socio-emotional skills in general. In addition, there was no significant gap between two core components, but five subcomponents stood out in a descending magnitude line of self-awareness>self-utilization, empathy>social skills>self-regulation. These significant findings provide constructive guidance needed for our research team to project instructional action plans in the subsequent phases. It also provokes further research on similar strands within Vietnam and beyond.